60.0k views
0 votes
-3/v=-6 simply as much as possible

1 Answer

4 votes
Hey!


In order to simplify this equation, we'll first have to multiply both sides of the equation by v. This will give us v on its own.

Original Equation :

(-3)/(v) = -6

New Equation {Added Multiply Both Sides by V} :

(-3)/(v) v=-6v

Solution {New Equation Solved} :

-3 = -6v

Now we'll switch sides to get v on the left side of the equation which is generally where we always want the variables to be located in these types of equations.

Old Equation :

-3 = -6v

New Equation {Switched} :

-6v=-3

Now we'll divide both sides by v to get v on its own.

Old Equation :

-6v = -3

New Equation {Added Divide Both Sides by V} :

(-6v)/(v) = (-3)/(v)

Solution {New Equation Solved} :

v = (1)/(2)

So, this means that in the equation
(-3)/(v) =-6,

v = (1)/(2).

Hope this helps!


- Lindsey Frazier ♥
User Yanis Boucherit
by
6.0k points